Treatment effect of CDKN1A on rheumatoid arthritis by mediating proliferation and invasion of fibroblast-like synoviocytes cells. (23rd September 2018) - Gang, X; Xu, H; Si, L; Zhu, X; Yu, T; Jiang, Z; Wang, Y
Summary: The objective of the present study was to evaluate the role of CDKN1A in rheumatoid arthritis (RA). Related gene expression data screened from Gene Expression Omnibus (GEO) were processed with network analysis. Protein–protein interaction was analysed through string database. Quantitative reverse transcription–polymerase chain reaction (qRT–PCR) was used to measure mRNA and microRNA expression. Cell proliferation and cell cycle were tested by MTT assay and flow cytometry, respectively. Transwell migration and invasion assay was used to test cell migration and invasion. CDKN1A screened by bioinformatics methods showed differential expression in RA cells compared with healthy controls (HC), and was at an important position in the protein–protein interaction network of RA. Compared with the HC group, CDKN1A was down-regulated in human RA synovium tissues and human fibroblast-like synoviocytes (HFLS). Contrary to CDKN1A silencing, CDKN1A over-expression significantly inhibited the proliferation and invasion of HFLS-RA, arrested HFLS-RA in G0/G1 phase and down-regulated the expressions of tumour necrosis factor (TNF)-α and interleukin (IL)-6, while it up-regulated the expression of IL-10. CDKN1A over-expression could also suppress phosphorylated signal transducers and activators of transcription 1 (pSTAT-1) expression. MiR-146a, highly expressed in RA tissues, could regulate CDKN1A negatively. Anti-146a suppressed cell proliferation and invasion, and at the same time enhanced IL-10 expression but inhibited IL-6, TNF-α and pSTAT-1 expression. The results indicated that CDKN1A over-expression, which could be enhanced by miR-146a suppression, inhibited the proliferation of invasion in HFLS-RA. This was probably a result of suppressed pSTAT-1, IL-6 and TNF-α expression and enhanced IL-10 expression. Graphical Abstract: